2013
DOI: 10.5897/ajar12.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blending fresh-saline water and discharge rate of drip on plant yield, water use efficiency (WUE) and quality of tomato in semi arid environment

Abstract: The use of alkali ground water constitutes a major threat to irrigated agriculture in semiarid parts of India. The entire arid and semiarid region in India is characterized by low rainfall and has the problems either of water scarcity or poor quality ground water and it can be better utilized for irrigation through drip irrigation system. An experiment was conducted on tomato crop at Central Institute of Post Harvest Engineering and Technology (CIPHET) Abohar, Punjab to study the effect of blending fresh and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…Water stress occurred throughout the growing season, and both dry matter content and sugar concentration are significantly increased during fruit ripening. Harmanto et al, [10] Singh et al [11] and other studies have reached the same conclusion. Based on the complexity and real-time of irrigation process, Chen et al [12] developed a water-saving irrigation management and decision support system software and made irrigation forecasts to determine the precise irrigation time and irrigation volume.…”
Section: Related Worksupporting
confidence: 56%
See 2 more Smart Citations
“…Water stress occurred throughout the growing season, and both dry matter content and sugar concentration are significantly increased during fruit ripening. Harmanto et al, [10] Singh et al [11] and other studies have reached the same conclusion. Based on the complexity and real-time of irrigation process, Chen et al [12] developed a water-saving irrigation management and decision support system software and made irrigation forecasts to determine the precise irrigation time and irrigation volume.…”
Section: Related Worksupporting
confidence: 56%
“…Based on previous researches [8][9][10][11][12][13][14][15][16], this paper combined fuzzy theory with neural network to make decisions for water-saving irrigation with T-S fuzzy neural network based on genetic optimization for greenhouse tomatoes. This method overcomes the problem of low accuracy in fuzzy system, and it has better effect than the system which only uses the artificial neural network (ANN).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies indicate that sensitivity and tolerance of crops to the effects of water salinity may vary among species and cultivars of a same species, and also depend on the climatic conditions of the region, type of soil, method of irrigation, plant development stage, among others (Aragão et al, 2009;Dias et al, 2011;Nangare et al, 2013;Medeiros et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Farooq et al (2021) found that the highest level of nitrogen produced tomatoes with a higher number of fruits and greater fruit firmness under varying irrigation water salinities. On the other hand, Nangare et al (2013) observed that the interaction effect of salinity and nitrogen significantly increased the number of leaves and seedling dry weight.…”
Section: Resultsmentioning
confidence: 95%